Assessing scientific publications by their impact. A possibility for a more accurate evaluation of researchers - Loidi, Javier (Mediterranean Botany, 2025)
The use of metrics in the evaluation of a researcher’s output is now a common practice and has a decisive influence on their career (metricracy). It is widespread to consider the Journal Impact Factor (JIF) as a means of assessing the quality and significance of a paper. It has been discussed that it is appropriate to use a metric that evaluates each paper based on its citations rather than the journal in which it was published. Other parameters such as the number of years since publication, the number of authors and their position in the author list are also discussed and a formula for scoring each published article is proposed.